Interaction of campylobacter species with antibody, complement and phagocytes. Issue 7 (July 1989) - Bernatowska, E; Jose, P; Davies, H; Stephenson, M; Webster, D
Abstract : The opsonisation of four different campylobacter species for human neutrophils was studied using a chemiluminescence system and electron microscopy. Opsonisation of Campylobacter fetus, Campylobacter coli, and Campylobacter jejuni was mediated by antibody and enhanced by complement. Antibody was not, however, required for the phagocytosis of Campylobacter pylori because it activates the classical pathway of complement directly. This unusual property may be important in the pathogenesis of C pylori associated gastritis and duodenal ulcer.